PENGGUNAAN MEDIA SOSIAL DAN MOTIVASI BELAJAR SISWA DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Resky Yulinda Putri; Tri Umari; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study entitled "The Use of Social Media and Student Motivation in SMK LABOR BINAAN FKIP UNRI PEKANBARU". Data from the Ministry of Communication and Informatics (Kemenkominfo) in its website (kominfo.com) year (2015) revealed internet users in Indonesia currently reach 63 million people. Of these, 95% use the internet to access social networks. The purpose of research: 1) To know the use of social media among students at SMK LABOR BINAAN FKIP UNRI PEKANBARU. 2) to know the motivation of student learning using social media at SMK LABOR BINAAN FKIP UNRI PEKANBARU. Research sample 140 people.Quantitative descriptive research method. Data collection techniques are questionnaires. Technique of data analysis percentage. The results of research using social media 100% of students access social media every day. Time spent> 3hrs / day, 3hrs / hour, 2hours / day, <1hr / day. Type of social media that is widely used Instagram, WhatsApp, Facebook, Line, Youtube, Twitter, BBM. the condition of accessing social media when gathering with friends, when time is empty, before sleep, waking, and when eating. In general, social media students use to find entertainment. The use of social media in general is in the low category. Motivation to learn the highest awards in learning. Student learning motivation using social media in general is in the medium category. Recommendations: 1) to teachers and parents of students to give more attention to students who use social media so that students' learning motivation is not low. 2) For other researchers interested in researching this subject it is advisable to undertake more detailed research or to add appropriate variables related to counseling guidance.Key Words: Social media, Motivation learning